Eddy covariance based surface‐atmosphere exchange and crop coefficient determination in a mountainous peatland. Issue 1 (22nd October 2018) - Gerling, Lars; Weber, Tobias K.D.; Reineke, Daniela; Durner, Wolfgang; Martin, Sabrina; Weber, Stephan
Abstract: In the soil–plant–atmosphere continuum, fluxes of water, energy, and carbon determine the water and carbon balance of peat bogs. We used eddy covariance (EC) measurements to study surface atmosphere exchange and its drivers above an ombrotrophic peat bog (Odersprungmoor) in the Harz Mountains, Germany, with nonideal measurement conditions during the growing season in 2013. For montane peatlands, only very few EC flux measurements exist due to site constraints, for example, surface slope, limited fetch, and frequent dew formation on open path sensors. The measured data were carefully filtered resulting in valid and representative fluxes for the bog. The evapotranspiration (ET) was further characterized by determining the adjusted crop coefficient ( K c* ) for July and August and comparing it with K c* values from 7 years of the FLUXNET site Mer Bleue bog, Ontario, Canada. While soil moisture was taken into consideration, the adjustment was nevertheless necessary as plant health and nutrient supply were not evaluated as required by FAO guidelines. Actual ET at OM was well described by the K c* model ( K c*  = 0.85, R 2  = 0.85). The primary control on ET was available energy and atmospheric conditions and, marginally, the soil moisture conditions. This K c* value is comparable to the calculated K c* values for MB, which ranged between 0.82 and 0.86 ( R 2 between 0.84 and 0.97). Since these K c* ranges are narrow for the different sites and years, we hypothesize that these values are good estimates for the true crop coefficients of Sphagnum ‐dominated peat bogs.